Analysis of the relationship between zoobenthos diversity, sediment characteristics, and mangrove density in the Fishery Port Areas of Bireuen Regency, Aceh - Azhar, Rossy; Izwar, Akmal; Mustaqim, Andy; Nugrahawati, Anis (Acta Aquatica: Aquatic Sciences Journal, 2025)
This study examines the relationship between zoobenthos diversity, sediment characteristics, and mangrove density in three fishery harbors in Bireuen District: PPI Peudada, PPI Jeumpa, and PPI Jangka. Data were collected using quadrat and line transects with purposive sampling. Peudada showed the highest zoobenthos diversity (H'=0.71) with low dominance (D=0.27) and medium sand substrate. Jeumpa and Jangka were dominated by tolerant species and coarse sand. True mangrove regeneration was more developed in Jeumpa and Jangka, while Peudada was dominated by non-mangrove vegetation. There is a strong relationship between sediment type, zoobenthos diversity, and mangrove structure. Fine sediments favored benthic diversity, while coarse sediments supported mangrove growth. The findings highlight the importance of integrated coastal ecosystem management to sustain ecological functions in fishery ports. Keywords: Bireuen; Coastal Ecosystem; Mangrove; Sediment; Zoobenthos